Application of Buoy Observations in Determining Characteristics of Several Typhoons Passing the East China Sea in August 2012 - Ningli Huang; Zheqing Fang; Fei Liu (Advances in Meteorology)
The buoy observation network in the East China Sea is used to assist the determination of the characteristics of tropical cyclone structure in August 2012. When super typhoon “Haikui” made landfall in northern Zhejiang province, it passed over three buoys, the East China Sea Buoy, the Sea Reef Buoy, and the Channel Buoy, which were located within the radii of the 13.9 m/s winds, 24.5 m/s winds, and 24.5 m/s winds, respectively. These buoy observations verified the accuracy of typhoon intensity determined by China Meteorological Administration (CMA). The East China Sea Buoy had closely observed typhoons “Bolaven” and “Tembin,” which provided real-time guidance for forecasters to better understand the typhoon structure and were also used to quantify the air-sea interface heat exchange during the passage of the storm. The buoy-measured wind and pressure time series were also used to correct the intensity of “Damrey” initially determined by CMA.